Ear Lobule Rejuvenation in Face-Lifting: The Role of Fat Augmentation. Issue 1 (January 2016) - Hammoudeh, Ziyad S.; Small, Kevin; Unger, Jacob G.; Stark, Ran; Rohrich, Rod J.
Abstract : Background: Ear lobule ptosis and deflation are characteristics of facial aging. A rhytidectomy without rejuvenation of a deflated ear lobule may fail to address all aspects of facial aging. Fillers have been used to treat ear lobule deflation; however, autologous fat transfer has never been utilized for ear lobule rejuvenation. This investigation studies the success of autologous fat transfer to the ear lobule as part of volume augmentation rhytidectomy. Methods: A retrospective review of patients who underwent rhytidectomy between 2000 and 2014 by a single surgeon was performed. Patients between 2000 and 2004 who did not receive autologous fat transfer served as controls (group A). Patients between 2010 and 2014 who received autologous fat transfer to the ear lobule formed the treatment group (group B). Three independent observers reviewed preoperative and postoperative photographs for both groups at 1 year postoperatively. The following ear lobule volume grading scale was applied to numerically assess the patients: concave = 0, flat = 1, convex = 2, and round = 3. Results: Groups A and B each consisted of 65 consecutive patients (130 ears). In group A, the mean preoperative ear lobule grading score was 1.20, and the mean postoperative score was 1.22 (mean difference, 0.02; P = 0.42). In group B, the mean preoperative ear lobule grading score was 0.98, and the mean postoperative score was 2.00 (mean difference, 1.02; P < 0.0001). Conclusion: In patients receiving autologous fat transfer to the ear lobule during rhytidectomy, there was a significant change from a deflated ear lobule preoperatively to a more voluminous lobule at 1 year postoperatively. Abstract : Supplemental Digital Content is available in the text.